Predictors of functional performance in school-aged children with Down syndrome - Gerlach-McDonald, Brianne, author; Daunhauer, Lisa A., advisor; Fidler, Deborah, advisor; Khetani, Mary, committee member (Colorado State University. Libraries, 2015)
This project examined whether executive functioning, language ability, and/or intelligence quotient predicts functional performance in children with Down syndrome, the most common neurogenetic syndrome associated with intellectual disability. Functional performance is the performance of tasks universal to all children-- such as self-care, mobility, and social interaction. Identifying patterns of functional performance in Down syndrome is critical as it is a foundation for optimal outcomes for the child, their family, and community. Executive functioning is an umbrella term used to describe thinking skills that are involved in goal-directed behavior. Children with Down syndrome are predisposed to specific areas of relative strengths and challenges in executive functioning, but it is unclear whether this phenotypic profile affects functional performance. Children with Down syndrome and students with mixed developmental disabilities were matched for mental and chronological age using the Leiter International Performance Scale-Revised. Functional performance and executive function were measured by parent-report, using the Pediatric Evaluation of Disability Inventory and the Behavior Rating Inventory of Executive Function- Preschool Version, respectively. Language and mental ability were measured using two standardized assessments, the Oral and Expressive Language Scales of the Oral and Written Language Scales and the Leiter International Performance Scale-Revised. Results indicated that children with Down syndrome and children with mixed developmental disabilities had similar functional profiles with strength in mobility and relative challenges in social function and self-care. Executive function was the only significant predictor of functional performance for relative children with Down syndrome, while intelligence quotient was the only significant predictor of functional performance for children with mixed developmental disabilities. Findings suggest differential targets for interventions to improve functional performance outcomes in children with Down syndrome and mixed developmental disabilities.